Aktivitas Antibakteri Ekstrak Tangkai dan Daun Begonia Multangula Blume. terhadap Porphyromonas Gingivalis - Nadya Haqque Santosa Putri; Dewi Nurdiwiyati; Sintia Lestari; Billyardi Ramdhan; Muhammad Efendi; Novik Nurhidayat (Jurnal Biologi Universitas Andalas, 2019)
Begonia multangula Blume. has acid sensation and it spread abundant on the western mountains of Java. While result of Periodontitis sufferer’s krevicular epitel investigation shows Porphyromonas gingivalis sticking portion are 5 – 20 times greater than another bacteria. Research about antibacterial activity of the stem and leaf extracts of B. multangula on P. gingivalis has been studied. This research using two methods of extraction i.e fresh extract and maseration with etanol and aquades as solvent. Volume extract tested are 10 µL and 20 µL with aquades and etanol 48% as negative control. This research using disk difution method with three replications. Incubation process during 40 hours in anaerob jar 37 ºC degree. The results showed that all of the extracts have bactericide activity toward P. gingivalis, while two negative controls has no show mentioned bactericide activity. The biggest bactericide activity owned by etanol extract of B. multangula’s stem, while the smallest bactericide activity owned by aquades extract of B. multangula’s leaf. Obstruction Power Index (Indeks Daya Hambat, IDH) of all extract inclined low.